The ontogeny of personality: Repeatability of social and escape behaviors across developmental stages in Siberian hamsters (Phodopus sungorus). Issue 6 (29th June 2021) - Adaniya, Catherine H.; Wellman, Cara L.; Demas, Gregory E.; Cusick, Jessica A.
Abstract: Animal personality is defined as behavioral tendencies that are consistent across time and contexts within an individual, but differ across individuals. Studies investigating personality typically examine individuals across short time periods or within a single life stage. Growing evidence suggests that personality may be less stable across life stages, highlighting the need to consider the effects of ontogeny on the expression of consistent behavioral traits. We investigated individual consistency in social and escape behaviors across developmental stages using Siberian hamsters ( Phodopus sungorus ). To determine whether individuals were consistent in these behaviors as juveniles and across developmental stages, we measured male and female social and escape behaviors twice as juveniles and once as adults. Individuals' social scores were significantly repeatable within the juvenile stage, but not across developmental stages. In contrast, escape scores were highly repeatable across developmental stages, with males' scores being more repeatable than females' scores. Our results support previous findings that personality traits, especially those associated with social behavior, are less stable across development, whereas behaviors associated with stress or coping may represent a more permanent feature of an individual's phenotype. Our results also indicate potential sex differences in long‐term repeatability of personality. Considering how ontogeny affects animal personality for males and females can provide insight into the evolution and mechanisms that maintain animal personality. Abstract : Individual repeatability of escape scores across developmental stages (Juvenile Trial 1 and Adult Trial). Highlights: Individuals' social scores were repeatable within the juvenile stage, but not across developmental stages Individuals' escape scores were highly repeatable across developmental stages Males' escape scores were more repeatable than females' escape scores